Prolyl-4 Hydroxylase 2 (PHD2) Deficiency in Endothelial Cells and Hematopoietic Cells Induces Obliterative Vascular Remodeling and Severe Pulmonary Arterial Hypertension in Mice and Humans Through Hypoxia-Inducible Factor-2α. Issue 24 (14th June 2016) - Dai, Zhiyu; Li, Ming; Wharton, John; Zhu, Maggie M.; Zhao, You-Yang
Abstract : Background—: Vascular occlusion and complex plexiform lesions are hallmarks of the pathology of severe pulmonary arterial hypertension (PAH) in patients. However, the mechanisms of obliterative vascular remodeling remain elusive; hence, current therapies have not targeted the fundamental disease-modifying mechanisms and result in only modest improvement in morbidity and mortality. Methods and Results—: Mice with Tie2 Cre-mediated disruption of Egln1 (encoding prolyl-4 hydroxylase 2 [PHD2]; Egln1 Tie2 ) in endothelial cells and hematopoietic cells exhibited spontaneous severe PAH with extensive pulmonary vascular remodeling, including vascular occlusion and plexiform-like lesions, resembling the hallmarks of the pathology of clinical PAH. As seen in patients with idiopathic PAH, Egln1 Tie2 mice exhibited unprecedented right ventricular hypertrophy and failure and progressive mortality. Consistently, PHD2 expression was diminished in lung endothelial cells of obliterated pulmonary vessels in patients with idiopathic PAH. Genetic deletions of both Egln1 and Hif1a or Egln1 and Hif2a identified hypoxia-inducible factor-2α as the critical mediator of the severe PAH seen in Egln1 Tie2 mice. We also observed altered expression of many pulmonary hypertension–causing genes in Egln1 Tie2 lungs, which was normalized in Egln1 Tie2 / Hif2a Tie2 lungs. PHD2-deficient endothelial cells promoted smooth muscle cell proliferation in part through hypoxia-inducible factor-2α–activated CXCL12 expression. Genetic deletion of Cxcl12 attenuated PAH in Egln1 Tie2 mice. Conclusions—: These studies defined an unexpected role of PHD2 deficiency in the mechanisms of severe PAH and identified the first genetically modified mouse model with obliterative vascular remodeling and pathophysiology recapitulating clinical PAH. Thus, targeting PHD2/hypoxia-inducible factor-2α signaling is a promising strategy to reverse vascular remodeling for treatment of severe PAH. Abstract : Supplemental Digital Content is available in the text.